Use of Phytase to Enhance Nutritional Value of Broiler Breeder Diets - Nusairat, B.; Qudsieh, R.; Brake , J. (International Journal of Poultry Science, 2018)
Objective: This study was designed to determine the effects of dietary phytase on broiler breeder grower and layer diets. Materials and Methods: Chicks received a common starter diet up to 42 days of age. Treatments were 0 (control), 300, 600 and 1200 FTU kg–1 phytase feed applied from 43 days to 4 replicate pens per treatment. Dietary calcium (Ca) was 0.7 and 2.7% while available phosphorus (AvP) was 0.35 and 0.12%, in the control grower and layer diets, respectively. Egg production, hatchability, fertility, egg quality, bone breaking strength, body weight (BW) and mortality to 64 weeks of age were measured. Data were analyzed using one-way ANOVA in 10 weeks quartile periods from 25-64 weeks of age as well as on an overall basis. Results: During the first quartile, phytase increased (p